A Model for Simulating FCR Prequalification Tests for Kaplan Turbines - Eriksson, Eddie (My University, 2024)
Abstract A Kaplan turbine was modeled in Simulink with the purpose of simulating prequalification tests for Frequency Containment Reserve (FCR) provision, based on technical requirements for FCR introduced in 2023. The model did not successfully predict fulfillment of steady-state requirements, and was too optimistic in its prediction of fulfillment of dynamic requirements. However, all tests predicted to fail also failed in real-world tests, indicating a potential use case for ruling out Kaplan turbines not suitable for FCR provision. A sensitivity analysis showed that simulation results were mostly unaffected by runner servo parameters, indicating a flaw in the model. Compensation with a first order low-pass filter significantly improved the accuracy of simulated dynamics. However, several model parameters, including the time constant for the low-pass filter, needed real-world tests for estimation. This reduced the likelihood of achieving high simulation accuracy ahead of conducting real prequalification tests. Using the simulated prequalification tests, methods for improving performance were explored. Both tuning the FCR controllers and the servos controlling guide vanes and runner blades were shown to improve dynamic performance, but tuning the servos improved the stability margins more. An approach to active power feedback was introduced and resulted in perfect fulfillment of the steady-state requirements. The dynamic performance requirements were not affected much, but the stability margins were severely worsened due to larger control movements at higher frequencies. The results suggested that fulfilling all technical requirements for FCR will be very challenging for Kaplan turbines. However, with increased market participation from other sources, this will likely not lead to insufficient FCR capacity in the near future.
Keywords: Keywords: Kaplan turbine, FCR, modeling, simulation, prequalification